Body Composition and Strength Parameters in Elite Judo Athletes 5 Years after Anterior Cruciate Ligament Reconstruction - Prill, Robert; Michel, Sven; Schulz, Robert; Coriolano, Hans-Joachim Appell (International Journal of Sports Medicine, 2019)
The purpose of this study was to investigate if there are still deficits in muscle mass or strength capabilities in elite judo athletes with a history of anterior cruciate ligament reconstruction (ACLR) after their return to the sport. Therefore, bioimpedance analysis, 3D-laser thigh circumference measurement and isokinetic dynamometry in a closed kinetic chain were used. The side-to-side differences were investigated in a group of judo athletes 5 years after ACLR (n=17) and compared with a group of healthy judo athletes (n=27). Neither thigh circumferences, nor muscle masses of the lower extremities differed in formerly injured judo athletes compared to healthy judo athletes. In contrast, isokinetic strength testing showed a significantly larger side-to-side difference of peak muscle force in formerly injured judo athletes (p=0.021). They provided significantly lower peak forces with the formerly injured leg than with the non-injured leg (p<0.001). The authors conclude that strength capabilities, but not body composition, remains altered in recovered judo athletes in mean 5 years after ACLR and definitely after their return to sports. This indicates that the focus of rehabilitation protocols and return to sports assessments should focus more on maximum strength capabilities.
Keywords: back to competition; anterior cruciate ligament reconstruction; isokinetic; bioimpedance; sports injury; closed kinetic chain